2014
DOI: 10.11604/pamj.2014.17.272.3268
|View full text |Cite
|
Sign up to set email alerts
|

Aspects épidemiocliniques et évolutifs chez 157 cas de leishmaniose cutanée au Maroc

Abstract: Connue au Maroc depuis la fin du XIX siècle, la leishmaniose cutanée (LC) constitue un problème de santé publique dans notre pays. Le but de notre travail est de décrire le profil épidémioclinique et l’évolution post thérapeutique chez les patients ayant une leishmaniose cutanée dans notre contexte. Nous avons effectué une étude rétrospective, basée sur l'exploitation des dossiers de malades ayant présenté une leishmaniose cutanée confirmée entre janvier 2003 et décembre 2012. Nous avons colligés 157 cas de le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
0
1
1
Order By: Relevance
“…Pentamidine (pentacarinat®) was by far the second highest with 3/42 (7.14%) use. Our findings were similar to those of Hjira et al in Morocco in 2014 19 , Nikiéma in Burkina Faso in 2002 16 , Diallo in Senegal in 2014 14 , and Bamba et al in Burkina Faso in 2013 9 , who noted the use of meglumine antimoniate (Glucantime®) as first-line therapy. This shows that there has been very little change in Leishmaniasis therapy 21 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Pentamidine (pentacarinat®) was by far the second highest with 3/42 (7.14%) use. Our findings were similar to those of Hjira et al in Morocco in 2014 19 , Nikiéma in Burkina Faso in 2002 16 , Diallo in Senegal in 2014 14 , and Bamba et al in Burkina Faso in 2013 9 , who noted the use of meglumine antimoniate (Glucantime®) as first-line therapy. This shows that there has been very little change in Leishmaniasis therapy 21 .…”
Section: Discussionsupporting
confidence: 90%
“…We identified twelve (12) clinical forms, with a predominance of ulcerative-crustal forms of 29.78%. This predominance of ulcerative-crustal forms (29.78%) was different to that of 40.2% found by Bamba et al in Burkina Faso in 2006 18 , and that of 53.1% recorded by Kéita et al in 2003 in Mali 19 , and at the 48% rate observed by Hjira et al in 2014 in Morocco. However, in all these studies as in ours, this ulcerative-crustal form was the predominant form.…”
Section: Discussioncontrasting
confidence: 60%
“…Le caractère clinique de cette lésion observée chez notre patient à type d'ulcération crouteuse est classique de celui des données de la littérature dans leur nombre et leur localisation [5][6][7]. Cependant cette localisation au visage et précisément à l'angle interne de l'oeil droit est rare, faisant évoquer d'autres pathologies telles que: lymphome cutané, la tuberculose cutanée et le granulome pyogénique.…”
Section: Discussionunclassified